Digital Parenting: Pelatihan Komunikasi Efektif Orang Tua dan Anak Usia Dini di Era Digital - Fitriani Dzulfadhilah; Rusmayadi; A. Sri Wahyuni Asti; Sri Rika Amriani H; Angri Lismayani (Jurusan Teknik Informatika dan Komputer, 2023)
The community service activity carried out is training to build effective communication between parents and children in the digital era. This service targets parents of early childhood at TK Negeri Pembina Makassar. There were 17 parents who participated in the training activities to build effective communication between parents and children in the digital era. The purpose of this service activity is to develop the ability of parents of early childhood at TK Negeri Pembina Makassar to develop effective communication with early childhood in the digital era. This service wants to increase the knowledge of parents of early childhood in building effective communication with their children in the digital era. The location of this service was carried out in the hall of TK Negeri Pembina Makassar. This activity involves cooperation with related parties. The implementation method used in this service is the lecture and discussion method on 17 parents of early childhood as participants in this activity. The results of this service activity were measured using a questionnaire that was directly distributed to parents and filled in after attending the training. The results of the service showed an increase in parents' knowledge of the characteristics of children in the digital era by 94%, an increase in parents' knowledge of appropriate parenting in the digital era by 82%, and also an increase in parents' knowledge on strategies for building effective communication with early childhood in the digital era by 88%.